2010
DOI: 10.1029/2010gl042488
|View full text |Cite
|
Sign up to set email alerts
|

New periodicity in Jovian decametric radio emission

Abstract: We report on the finding of a new periodicity in the Jovian decametric radio emission (DAM). Periodic bursts of non‐Io component of DAM which recur with a period 1.5% longer than the Jupiter rotation (System III) have been found in the dynamic radio spectra acquired by STEREO/WAVES, Wind/WAVES and Cassini/RPWS during the years 2002–2008. Typically, the bursts appear very periodically over several Jovian days with a decreasing intensity and they display a negative frequency drift. All the bursts were detected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Using the fact that Jovian radio emission is emitted in a hollow cone attached to the Jovian magnetic field or to the Io flux tube and the known rotation rate of Jovian magnetosphere (9.925 h) or Io's orbital period (42.46 h) as well as distances between Jupiter and each of the spacecraft the DAM emission can be identified by means of the time difference between sequential detection of the radio emission from the same radio source by the two spacecraft separated in space. In particular, this time delay consists of the light travel time difference between a radio source and an observer and the time interval which is necessary to rotate the radio beam by the angular separation (as seen from Jupiter) between the two spacecraft (see Panchenko et al, 2010). Therefore, the stereoscopic observations allow to (1) separate Jovian arc-like radio emission from the solar radio bursts and (2) unambiguously distinguish between Io and non-Io controlled component of DAM.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the fact that Jovian radio emission is emitted in a hollow cone attached to the Jovian magnetic field or to the Io flux tube and the known rotation rate of Jovian magnetosphere (9.925 h) or Io's orbital period (42.46 h) as well as distances between Jupiter and each of the spacecraft the DAM emission can be identified by means of the time difference between sequential detection of the radio emission from the same radio source by the two spacecraft separated in space. In particular, this time delay consists of the light travel time difference between a radio source and an observer and the time interval which is necessary to rotate the radio beam by the angular separation (as seen from Jupiter) between the two spacecraft (see Panchenko et al, 2010). Therefore, the stereoscopic observations allow to (1) separate Jovian arc-like radio emission from the solar radio bursts and (2) unambiguously distinguish between Io and non-Io controlled component of DAM.…”
Section: Observationsmentioning
confidence: 99%
“…Generally, non-Io DAM is a highly variable and sporadic radio emission which appears in a form of arcs in time–frequency coordinates and modulated by the rotation of the Jovian magnetosphere. Recently, Panchenko et al (2010) and Panchenko and Rucker (2011) have reported findings of the new type of Io independent radio bursts of DAM—periodic non-Io DAM burst. This emission is observed in the decametric frequency range (typically 5–12 MHz) in the form of arc-like radio bursts.…”
Section: Introductionmentioning
confidence: 99%
“…These latitudinal extended fingers may be a plasma source which supplies the cyclotron maser in the auroral region. Therefore, it has been suggested that the interchange instability in the Io torus, triggered by the solar wind pulses, may be a possible generation mechanism of the periodic non-Io DAM bursts (Panchenko et al, 2013). Besides the main group of periodic bursts, two other groups of periodic features, rarely observed in the radio spectra, were found.…”
Section: Jupiter Radio Emissionmentioning
confidence: 98%
“…The non-Io component of the DAM is a highly variable and sporadic radio emission, generally modulated by the rotation of the Jovian magnetosphere. Recently, Panchenko et al (2010Panchenko et al ( , 2013 and Panchenko and Rucker (2011) reported on the finding of new types of intense non-Io DAM bursts recorded by STEREO/WAVES, Wind/Waves and Cassini/RPWS space borne radio instruments in a frequency range from 5 MHz to 12-16 MHz, which are rarely observable on the Earth due to ionospheric cut-off below 10 MHz. The examples of these bursts are presented in Fig.…”
Section: Jupiter Radio Emissionmentioning
confidence: 99%
See 1 more Smart Citation